A Study On The Effectiveness Of Blog In Learning Process (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Information Technology has provided immediacy to education. Ablog-portmanteauof the  term web log. A weblog is a Website that consists of a series of entries arranged in reverse chronological  order, often updated on frequently with new information about particular topics. The information can  be written by the site owner, gleaned from other Websites or other sources, or contributed by users. Blogs can be a place where students reflect on readings, much as analog journaling was used as  a pedagogical tool in the past. Objective: This study was designed to identify the effectiveness of  blog, as a part of their education experience in the process of learning and interacting with their  co-students. Method: In the present study, samples of 100 college students were drawn from Hotel  Management discipline. They were administered 20-items of usage of Blog Scale. The collected data  were statistically analyzed by using mean, standard deviation and t – test. Results: The study indicated  that female and male students have significant effectiveness of BLOG usage in their learning process.  Recently, blogs have begun to emerge as a useful type of educational technology. Conclusion : Blogs  can be effective educational technology to which will facilitate learning for Gen. Y in this constantly  changing scenario.
Keywords: Information Technology; Learning; Blog